Hermeneutic Change of the Scientific Approach to Myths and Function of Symbols in the Cultures of the Ancient Middle East - Slivka, Daniel (Communications - Scientific letters of the University of Zilina, 2018)
In Slovakia, the older generations consider everything connected with religion a priori in the negative sense, because the previous regime led them to treat all such religious interpretations of life as legends or fairy tales. However, in the scientific world today, there is a significant change in the approach to the ancient literature, to its myths and old stories - epic poems of the humanity. In the absolute terms, myth communicates its content via symbols which convey its inner meaning. Nowadays, myths, epic poems, ancient literary works and literary units are considered to be narrative literary genres that were used by an archaic man for an explanation of events and facts that s/he could not explain in a satisfactory way or for hiding what is today referred to as scientific knowledge.